IN SITU DEMONSTRATION OF DNA HYBRIDIZING WITH CHROMOSOMAL AND NUCLEAR SAP RNA IN CHIRONOMUS TENTANS - Lambert, B. (The Rockefeller University Press, 1972)

(untitled)
Cytological hybridization combined with microdissection of Chironomus tentans salivary gland cells was used to locate DNA complementary to newly synthesized RNA from chromosomes and nuclear sap and from a single chromosomal puff, the Balbiani ring 2 (BR 2). Salivary glands were incubated with tritiated nucleosides. The labeled RNA was extracted from microdissected nuclei and hybridized to denatured squash preparations of salivary gland cells under conditions which primarily allow repeated sequences to interact. The bound RNA, resistant to ribonuclease treatment, was detected radioautographically. It was found that BR 2 RNA hybridizes specifically with the BR 2 region of chromosome IV. Nuclear sap RNA was fractionated into high and low molecular-weight RNA; the former hybridizes with the BR 2 region of chromosome IV, the latter in a diffuse distribution over the whole chromosome set. RNA from chromosome I hybridizes diffusely with all chromosomes. Nucleolar RNA hybridizes specifically with the nucleolar organizers, contained in chromosomes II and III. It is concluded that the BR 2 region of chromosome IV contains repeated DNA sequences and that nuclear sap contains BR 2 RNA.